MULTIPLICITY, COMPLEXITY, CIRCULATION AND MEDIATIZATION - Jaffe, Alexandra (Revista da Anpoll, 2016)
The aim of this text is to reflect upon the concepts of language, multiplicity, language ideology, metapragmatic regime and scale, among others that should be problematized in contemporary research which were, in one way or another, objects of discussion during the “School of Advanced Studies in Language and Society – Mobility at large” held in August, 2015, and organized by UNICAMP/UNIRIO in collaboration with other Brazilian universities. Ethnographic data collected in the development of my own research projects in Corsica will be referred to in my reflections about the concepts here revisited. This work is licensed under a Creative Commons Attribution 3.0 License.